A COMPANY PROFILE FOR IBIS SURABAYA CITY CENTER HOTEL - Grace Hennessy; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
Company profile is a description of the company history, resources, structure, performance, and reputation. Therefore, company profile is very important for the hotel and it also plays an important role for business communication because it provides the useful information of the hotel that can help the employees to get the product knowledge about the hotel. Also, it will help the customers when they want to stay in the hotel. As we know, ibis Surabaya City Center Hotel did not have the written company profile that can be very useful for the hotel. Therefore, ibis has to make the company profile for the hotel. By having the company profile, the hotel can attract new customers because many people will see the profile of the hotel. Moreover, this company profile will make an impact on the sales of the hotel because it is related with the promotion of the hotel